2001
DOI: 10.1038/ng782
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Pten in mouse brain causes seizures, ataxia and defects in soma size resembling Lhermitte-Duclos disease

Abstract: Initially identified in high-grade gliomas, mutations in the PTEN tumor-suppressor are also found in many sporadic cancers and a few related autosomal dominant hamartoma syndromes. PTEN is a 3'-specific phosphatidylinositol-3,4,5-trisphosphate (PI(3,4,5)P3) phosphatase and functions as a negative regulator of PI3K signaling. We generated a tissue-specific deletion of the mouse homolog Pten to address its role in brain function. Mice homozygous for this deletion (PtenloxP/loxP;Gfap-cre), developed seizures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
431
3
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(469 citation statements)
references
References 45 publications
32
431
3
3
Order By: Relevance
“…Similarly, the focal lesions in LDD rarely contain proliferative cells, as distinct from malignancies in which the second allele of PTEN has been inactivated by mutation. Further, some dysplastic neurons are ectopically placed in the molecular layer in LDD, similar to ectopically positioned granule neurons resulting from a neuronal migration defect in the mouse model (Backman et al, 2001;Kwon et al, 2001;Abel et al, 2005). Indeed, deletion of Pten in multiple neuronal types during development results in profound defects in migration and patterning in brain (Backman et al, 2001;Groszer et al, 2001;Kwon et al, 2001;Marino et al, 2002;Yue et al, 2005).…”
Section: Germline Mutations Of Pten Cause Neurological Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the focal lesions in LDD rarely contain proliferative cells, as distinct from malignancies in which the second allele of PTEN has been inactivated by mutation. Further, some dysplastic neurons are ectopically placed in the molecular layer in LDD, similar to ectopically positioned granule neurons resulting from a neuronal migration defect in the mouse model (Backman et al, 2001;Kwon et al, 2001;Abel et al, 2005). Indeed, deletion of Pten in multiple neuronal types during development results in profound defects in migration and patterning in brain (Backman et al, 2001;Groszer et al, 2001;Kwon et al, 2001;Marino et al, 2002;Yue et al, 2005).…”
Section: Germline Mutations Of Pten Cause Neurological Abnormalitiesmentioning
confidence: 99%
“…Although patients have inherited one mutant copy of PTEN, the dysplastic cells have either complete loss of PTEN expression or express only the mutant allele, which is accompanied by elevated phosphorylated AKT (Iida et al, 1998;Zhou et al, 2003;Abel et al, 2005). The features of LDD were recapitulated in mouse models where Pten was conditionally deleted late in development of granule neurons of the cerebellum resulting in a cell-autonomous loss of size regulation (Backman et al, 2001;Kwon et al, 2001). In the mouse, the size of Ptendeficient granule neurons progressively increases without evidence of abnormal proliferation.…”
Section: Germline Mutations Of Pten Cause Neurological Abnormalitiesmentioning
confidence: 99%
“…Notch signaling is thought to maintain ''stemness'' and to prevent exit from the cell cycle and maturation (Basak and Taylor, 2009). However, its role in adult neurogenesis remains unclear, primarily because Notch plays so many other roles in maturation, neuroplasticity, and survival (Carlson and Conboy, 2007;Corbin et al, 2008 (Backman et al, 2001;Kwon et al, 2001;Groszer et al, 2001). Conditional knockout of Pten in neural stem cells revealed that Pten is indispensable for proper control of neural stem cell proliferation and self-renewal in the developing brain (Groszer et al, 2001).…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…Additionally, PTEN was shown to control ovarian follicle activation and therefore reproduction of mammals (Reddy et al, 2008). The roles of PTEN in the development and function of specific organs/tissues, such as brain, heart, and bone, have also been reported (Backman et al, 2001;Groszer et al, 2001;Kwon et al, 2001Kwon et al, , 2006Crackower et al, 2002;Liu et al, 2007;Oudit et al, 2008).…”
Section: Pten As a Multifunctional Biological Regulatormentioning
confidence: 98%
“…The strong evidence for this argument is that many physiological abnormalities and tumorigenesis caused by the loss of PTEN function are associated with Akt activation and can be attenuated by pharmacological inhibition of PI3K, Akt or downstream components such as, mammalian Target of Rapamycin (mTOR) (Backman et al, 2001;Groszer et al, 2001;Kwon et al, 2001Kwon et al, , 2006Crackower et al, 2002;Liu et al, 2007;Oudit et al, 2008).…”
Section: Pten As a Multifunctional Biological Regulatormentioning
confidence: 99%